Application of Service Standards in the Management of Certificates of Good Attitude and Driver's License at the West Nusa Tenggara Police Office - Razak, Abdul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
The Republic of Indonesia Police are currently improving themselves to gain public sympathy, one of which is by providing satisfactory service. This is a concrete step by the police in creating a humane and friendly police force. In addition, providing excellent service to the community in the form of administrative services with good behavior and driving licenses is one proof of the good performance of the Indonesian police, thereby increasing public confidence in the role of the police in society. Based on this explanation, this research was conducted to see the performance of police services in the city of Mataram, Lombok, West Nusa Tenggara. To achieve this goal, the scientific method is used in the form of descriptive quantitative testing by presenting natural/as-is respondents' responses. The research informants were people who made documents of good behavior and driving licenses at the Mataram city police office during the period January - August 2022. The number of correspondents involved in this study were 400 people, who were taken at simple random. Based on the survey results, information was obtained that the community was satisfied with the services provided by the Mataram city police for the management of good behavior certificates and driving licenses. The community feels that the services provided are in accordance with procedures, on time, and the attitude of the service staff is friendly.